SARS-CoV-2 ORF 3a-mediated currents are inhibited by antiarrhythmic drugs - Wiedmann, Felix Tobias; Boondej, Emika; Stanifer, Megan; Paasche, Amelie; Kraft, Manuel; Prüser, Merten; Seeger, Timon; Uhrig, Ulrike; Boulant, Steeve; Schmidt, Constanze (Europace, 2024)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been linked to cardiovascular complications, notably cardiac arrhythmias. The open reading frame (ORF) 3a of the coronavirus genome encodes for a transmembrane protein that can function as an ion channel. The aim of this study was to investigate the role of the SARS-CoV-2 ORF 3a protein in COVID-19-associated arrhythmias and its potential as a pharmacological target.Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) and cultured human fibroblasts were infected with SARS-CoV-2. Subsequent immunoblotting assays revealed the expression of ORF 3a protein in hiPSC-CM but not in fibroblasts. After intracytoplasmic injection of RNA encoding ORF 3a proteins into Xenopus laevis oocytes, macroscopic outward currents could be measured. While class I, II, and IV antiarrhythmic drugs showed minor effects on ORF 3a-mediated currents, a robust inhibition was detected after application of class III antiarrhythmics. The strongest effects were observed with dofetilide and amiodarone. Finally, molecular docking simulations and mutagenesis studies identified key amino acid residues involved in drug binding.Class III antiarrhythmic drugs are potential inhibitors of ORF 3a-mediated currents, offering new options for the treatment of COVID-19-related cardiac complications.